Blueberry Extracts as a Novel Approach to Prevent Ozone-Induced Cutaneous Inflammasome Activation. (14th August 2020) - Pambianchi, Erika; Ferrara, Francesca; Pecorelli, Alessandra; Woodby, Brittany; Grace, Mary; Therrien, Jean-Philippe; Lila, Mary Ann; Valacchi, Giuseppe
Abstract : The World Health Organization estimates that 7 million people die every year due to pollution exposure. Among the different pollutants to which living organism are exposed, ozone (O3 ) represents one of the most toxic, because its location which is the skin is one of the direct tissues exposed to the outdoor environment. Chronic exposure to outdoor stressors can alter cutaneous redox state resulting in the activation of inflammatory pathways. Recently, a new player in the inflammation mechanism was discovered: the multiprotein complex NLRP1 inflammasome, which has been shown to be also expressed in the skin. The topical application of natural compounds has been studied for the last 40 years as a possible approach to prevent and eventually cure skin conditions. Recently, the possibility to use blueberry (BB) extract to prevent pollution-induced skin toxicity has been of great interest in the cosmeceutical industry. In the present study, we analyzed the cutaneous protective effect of BB extract in several skin models (2D, 3D, and human skin explants). Specifically, we observed that in the different skin models used, BB extracts were able to enhance keratinocyte wound closure and normalize proliferation and migration responses previously altered by O3 . In addition, pretreatment with BB extracts was able to prevent ozone-induced ROS production and inflammasome activation measured as NRLP1-ASC scaffold formation and also prevent the transcripts of key inflammasome players such as CASP1 and IL-18, suggesting that this approach as a possible new technology to prevent cutaneous pollution damage. Our data support the hypothesis that BB extracts can effectively reduce skin inflammation and be a possible new technology against cutaneous pollution-induced damage.